2021
DOI: 10.3390/foods10051051
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Comparison and Classification of Volatile Compounds in Peels of 40 Apple Cultivars by HS–SPME with GC–MS

Abstract: Aroma is an important quality indicator for apples and has a great influence on the overall flavour and consumer acceptance. However, the information of the aroma volatile compounds in apple peels is largely unknown. In this study, evaluation of volatile compounds in peels of 40 apple cultivars was carried out using headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography-mass spectrometry (GC-MS). A total of 78 volatile compounds were identified, including 47 esters, 12 aldehydes, 5 alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…The types of volatile compounds in the Jonagold apple were more than that in the Granny Smith apple. Among these volatiles, esters were the predominant compounds in the Jonagold apple, accounting for more than 60% of the total volatiles, which was consistent with previous report that esters were the most abundant group that contribute mainly to the sweet and fruity odors of apple fruits [11,30]. Moreover, hexyl acetate, confers a sweet and fruity odor with floral notes, was the most plentiful ester in the Jonagold apple, which was in accordance with the results of previous studies [31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The types of volatile compounds in the Jonagold apple were more than that in the Granny Smith apple. Among these volatiles, esters were the predominant compounds in the Jonagold apple, accounting for more than 60% of the total volatiles, which was consistent with previous report that esters were the most abundant group that contribute mainly to the sweet and fruity odors of apple fruits [11,30]. Moreover, hexyl acetate, confers a sweet and fruity odor with floral notes, was the most plentiful ester in the Jonagold apple, which was in accordance with the results of previous studies [31].…”
Section: Discussionsupporting
confidence: 91%
“…The MdAFS as well as the MdHMGS , MdHMGR and MdFPPS genes in this pathway were all upregulated in Jonagold apples compared with the Granny Smith apple, might be responsible for high production of α-farnesene. In addition, phenylpropenes, such as eugenol, estragole and isoestragole, also contribute to apple aroma and these compounds are derived from the phenylpropanoid pathway [ 17 , 30 ]. It has been reported that estragole imparts a spicy and aniseed note to ‘Ellison Orange’ and ‘Royal Gala’ apples [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than 300 aromatic compounds have been identified in apples, including esters, alcohols, aldehydes, acids, ketones, and terpenoids ( Yang S. et al, 2021 ). Esters are the most important determinant of the aroma of ripe apples, followed by alcohols ( Espino-Díaz et al, 2016 ).…”
Section: Volatile Compositionmentioning
confidence: 99%
“…Esters are typically generated by the dehydration of hydroxy fatty acids [31], with a low odor threshold. They have creamy and fruity aromas and are essential components of an odor [32]. Baking defatted tiger nut flour generated γ-undecanolactone, and its relative content gradually increased, enhancing peanut and nutty aromas.…”
Section: Vocs In Defatted Tiger Nut Flourmentioning
confidence: 99%